Asynchonous distributed components: concurrency and determinacy - Caromel, Denis (2006)
Based on the imp&-calculus, ASP (Asynchronous Sequential Processes) de nes distributed applications behaving deterministically. This article extends ASP by building hierarchical and asynchronous distributed components. Components are hierarchical - a composite can be built from other components, and distributed - a composite can span over several machines. This article also shows how the asynchronous component model can be used to statically assert component determinism.